Analysis of the Values of Religious Moderation in Indonesian Local Wisdom Culture - Sameto, Mayang Belia; Syahminal, Syahminal; Marfiyanti, Marfiyanti; Ahmad, Nurasiah; Yanti, Novia; Bahri, Muhammad Fahreza (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Local wisdom is an integral part of a community's cultural identity, passed down from generation to generation. These values ​​play an important role in maintaining social harmony and strengthening the spirituality and morality of individuals in society. This research aims to analyze the religious and social values ​​of local wisdom culture in Indonesia. Local wisdom is an integral part of a community's cultural identity, passed down from generation to generation. This research uses qualitative methods with a phenomenological approach. this research examines how these values ​​are manifested in a series of rituals and celebrations of Tabuik, and how they support character and moral education in society. Data collection through observation, interviews with traditional leaders, religious leaders, and cultural actors Tabuik, as well as analysis of related documents. All data was analyzed using the Milles & Huberman interactive thematic analysis model technique. The research results show that culture Tabuik not only commemorates historical events in Islam but also functions as a medium for Islamic education that teaches the values ​​of patience, sacrifice, and brotherhood. Social values ​​such as cooperation and deliberation are also at the core of this cultural practice, strengthening family ties and encouraging active community participation in cultural preservation. This research confirms the importance of culture Tabuik as a culture of local wisdom in maintaining the religious and social identity of society in the modern era.